A Rare Case of Aortoatrial Fistula from Streptococcal Endocarditis. (5th July 2017) - Arshad, Hammad; Young, Meilin; Rali, Parth
Abstract : We represent an unfortunate case of postinfluenza streptococcal endocarditis in a 34-year-old healthy male. He presented with hypoxic respiratory failure and was found to have mitral and aortic valve vegetation. Hospital course was complicated by the presence of an aortoatrial fistula from an aortic root abscess, persistent septic shock, and multiorgan failure.